2018
DOI: 10.1038/s41416-018-0104-z
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of VEGFR TKI therapy after progression on immune combination therapy in metastatic renal cell carcinoma

Abstract: VEGFR TKIs have clinical activity in mRCC refractory to IC therapy, possibly impacted by the mechanism of prior combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 18 publications
4
32
1
Order By: Relevance
“…In one study, 20/56 received axitinib after progression on an ICI with a median TTF of 10.0 (0.2+, 19.3), one-year survival rate of 69 % (34,88), and ORR of 16 % [25]. Similarly, a second study reported 14/28 patients who received axitinib after progression on an ICI with a median PFS of 6.4 months (4.7-8.1) and an ORR of 29% [24]. In patients progressing on nivolumab and ipilimumab, the median PFS with subsequent axitinib treatment was 7 months (95% CI, 5-NR) [26].…”
Section: Axitinibmentioning
confidence: 98%
See 4 more Smart Citations
“…In one study, 20/56 received axitinib after progression on an ICI with a median TTF of 10.0 (0.2+, 19.3), one-year survival rate of 69 % (34,88), and ORR of 16 % [25]. Similarly, a second study reported 14/28 patients who received axitinib after progression on an ICI with a median PFS of 6.4 months (4.7-8.1) and an ORR of 29% [24]. In patients progressing on nivolumab and ipilimumab, the median PFS with subsequent axitinib treatment was 7 months (95% CI, 5-NR) [26].…”
Section: Axitinibmentioning
confidence: 98%
“…Few retrospective analyses have evaluated the efficacy of targeted treatment in patients who have disease progression on ICI-based therapy [23][24][25]. The ORR ranged from 13-29% and PFS or Time to Treatment Failure (TTF) ranged from 6.4-6.6 months.…”
Section: What Comes After Iomentioning
confidence: 99%
See 3 more Smart Citations